Evaluation of Sweet Blue Lupin (Lupinus angustifolius L.) Intercropped with Maize (Zea mays L.) at Different Planting Time Under Irrigation in the Highlands of Ethiopia - Gebeyaw Abel; Likawent Yeheyis; Firew Tegegne; Bimrew Asmare (Turkish Journal of Agriculture: Food Science and Technology)
A field experiment was conducted to evaluate the performance of sweet blue Lupin intercropped with maize at different planting time under irrigation in Ethiopia. For the experiment, sweet lupin (cultivar Sanabor) and Maize (cultivar PBH 3253) were used. The experiment was conducted in a randomized complete block design with four replications. The treatments were sweet lupin intercropped with maize simultaneously, 1, 2, 3, 4 and 5 weeks after maize planting. Sole maize was planted as control. Maize was planted in rows with spacing of 75 cm and 30 cm between rows and between plants, respectively. Lupin was planted between two maize rows (one maize row: two lupin row) 22.5 cm apart from maize row. The distance between lupin plants is 7 cm. In addition, maize rows were top-dressed N-fertilizer at the rate of 100 Kg ha-1 by dividing in to two at planting and at vegetative stage. Intercropping time had a significant effect on yield and yield components of sweet lupin, but not on maize. Lupin intercropped simultaneous with maize gave significantly higher dry matter and seed yield 1.05 and 1.71t/ha, respectively as compared to the four intercropping dates. Maize grain yield and maize stover yield were not affected by sweet lupin intercropping dates. This study showed that sweet lupin intercropped simultaneously with maize could be optimum sowing date for better grain and dry matter yield of sweet lupin without affecting maize grain and stover yield under irrigation condition.